Estimulación cognitiva y su influencia en las funciones ejecutivas de un adulto mayor del Centro Gerontológico El Buen Vivir Babahoyo - Arteaga Bermello, Angelica Amirelis (2020)
The elderly adult is going through a series of changes in different aspects, these changes could be normal but along with these changes, cognitive deterioration also occurs, and even more when the elderly adult is surrounded by risk factors, one of them is isolation and is like this how the elderly adult stars losing his abilities in the execution of different activities that involve mental processes, that's why this study proposes cognitive stimulation to improve executive functions, aimed to the elderly adult where cognitive stimulation techniques are applied according to their condition, for this particular case a set of techniques were implemented, such as the interview, the observation, psychometric tests, each of them with their respective instrument, which helped to establish a diagnosis to develop a psychotherapeutic design afterwards